Analisis Kesehatan Bank Menggunakan Metode RGEC di Bank BJB Periode 2019-2023 - Nurhasanah, Dinda; Huda, Badriyatul (Jurnal Dimamu, 2025)
Based on the results of observations, the background to this research is that there are several financial ratios that are experiencing fluctuations as well as to determine the level of bank health at Bank BJB for the 2019-2023 period. This research aims to determine the health level of Bank BJB for the 2019-2023 period using the RGEC method. The research factors used are Risk Profile, Good Corporate Governance, Earning and Capital factors. The type of research in this report is descriptive quantitative. The data used is secondary data in the form of BJB Bank financial reports and the Financial Services Authority (OJK) website. The research results show that the health level of Bank BJB according to the Risk Profile factor for NPL received the title Very Healthy and for LDR Fairly Healthy. The Good Corporate Governance factor received a healthy predicate. The Earning Factor for NIM received the title Very Healthy and for ROA Healthy. And the Capital CAR Factor has the title of Very Healthy. The data anakysis used is data collection, data reduction, data presentation and conclusions.